Immigration Control On Foreign Visiting Permit In Southeast Sulawesi - Rizki Putri Meilinda (Faculty of Law, University of Mataram, 2017)
This study aims to find and explain the immigration control system on foreign residency permits conducted by the First Class Immigration Office of Kendari City as well as to find and explain the immigration control on the abuses of visitor visas by foreigners in Southeast Sulawesi. This type of research is empirical sociological research by collecting data by examining primary data in the form of interviews to secondary data that is available in the field data and examine the facts that exist, in line with the observations made in the field and then reviewed based on relevant legislation to solve the problem . Data obtained from the results of both primary and secondary data were analyzed qualitatively using theoretical basis then presented in a descriptive. The results of this study indicate that the immigration control system on foreign residency permits conducted by the Immigration Office Class I Kendari City there are 2 (two) types of administrative supervision and field supervision. Administrative control is done by checking the validity of immigration documents in the form of travel documents or sponsorship and visit permits and by the immigration. while field supervision is supervised by direct disbursement to any company that has a foreign worker and monitors the sponsor or company on the validity of the residence permit including open supervision and closed supervision, and Immigration Control on the abuses of visa visits by foreigners in Southeast Sulawesi can be done by way of prevention prior to the occurrence of a law violation in the form of periodic observation / surveillance, disguise and acting as intelligence as well as supervision is done in the form of countermeasures in this case the visit visa abuse by following up and processing legally and deporting for foreigners who proven to abuse visa Southeast Sulawesi. Keywords: Immigration control, residence permit.